1992
DOI: 10.1104/pp.98.2.569
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of γ-Linolenic and Eicosapentaenoic Acids by Algae

Abstract: The pharmaceutical interest and limited availability of y-linolenic acid (GLA) and eicosapentaenoic acid (EPA) prompted the search for genetic means for increasing the production of these fatty acids from algal sources. Cell lines of Spirulina platensis and Porphyridium cruentum resistant to the growth inhibition of the herbicide Sandoz 9785 were selected by serial transfers of the culture in the presence of increasing concentrations of the herbicide. The resistant cell lines of S. platensis overproduced GLA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…The amount of total fatty acids in the cyanobacterium (3.38% of dry wt) is quite in the range (2.4-4.8%) reported in different Spirulina strains although in the latter case, GLA content varied from 8-31.7% of the fatty acid (Cohen et al 1987). GLA (12.5% of total fatty acid) as measured presently, is in the range of other cyanobacteria such as Synechocystis PCC 6803 (13-26%; Wada & Murata 1990) and Spirulina (21%) (Cohen et al 1992). Interestingly, a comparable level of GLA i.e.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The amount of total fatty acids in the cyanobacterium (3.38% of dry wt) is quite in the range (2.4-4.8%) reported in different Spirulina strains although in the latter case, GLA content varied from 8-31.7% of the fatty acid (Cohen et al 1987). GLA (12.5% of total fatty acid) as measured presently, is in the range of other cyanobacteria such as Synechocystis PCC 6803 (13-26%; Wada & Murata 1990) and Spirulina (21%) (Cohen et al 1992). Interestingly, a comparable level of GLA i.e.…”
Section: Resultsmentioning
confidence: 79%
“…GLA overproduction in the herbicide-resistant S. platensis could reach only 2% (23.6% of total fatty acid) (Cohen et al 1992). The latter investigators observed that GLA content in three Spirulina strains (optimum growth 35°C) was maximum at 30 or 35°C thus suggesting that temperature conditions optimum for general growth, also favoured GLA synthesis.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…An alternative promising source for GLA production is Spirulina platensis (4,6). Unlike fungi, which should be grown in sophisticated bioreactors, the cyanobacteria can be grown in large open ponds (2,17).…”
Section: Introductionmentioning
confidence: 99%
“…As the fatty acid composition is largely affected by environmental conditions, many studies have already been carried out based on varying the nutritional and physical conditions (Chojnacka and Noworyta 2004;Cohen et al 1987;Costa et al 2004;Mahajan and Kamat 1995), mutating to increase the GLA content (Cohen et al 1992;Tanticharoen et al 1994), and adding exogenous nutrients to the medium (Khoomrung et al 2008;Narayan et al 2005;Quoc et al 1994). In a previous study, the growth and GLA content of S. platensis were enhanced when culturing under dark conditions and using a mixotrophic culture with a high concentration of a glucose-tolerant mutant (Choi et al 2008).…”
Section: Introductionmentioning
confidence: 97%